Ekstraksi dan Karakterisasi Gelatin dari Kulit Ayam dengan Praperlakuan Asam Sitrat - Armayanti Akhiriyah Parinduri; Miftahul Khair (MASALIQ, 2026)
Although many studies have been conducted on gelatin from poultry waste, research that specifically discusses the characterization of chicken skin gelatin extracted using citric acid pretreatment and water bath heating remains limited. This study aims to evaluate the physicochemical characteristics and molecular structure of broiler chicken skin gelatin extracted with 1.3% citric acid pretreatment. This study used a laboratory experimental approach. Data were collected through tests of yield, moisture content, ash content, pH, viscosity, and Fourier Transform Infrared (FTIR) analysis, and were then analyzed descriptively and compared with gelatin quality standards. The results show that chicken skin gelatin had a yield of 11.73%, moisture content of 9.21%, ash content of 2.84%, pH of 7.35, and viscosity of 3.23 cP. All of these parameters met the gelatin quality standards based on SNI, while the viscosity and pH values remained within the GMIA standard range. FTIR analysis showed the presence of Amide A at 3280 cm⁻¹, Amide I at 1631 cm⁻¹, Amide II at 1533 cm⁻¹, and Amide III at 1239 cm⁻¹, indicating the transformation of collagen into gelatin. The conclusion of this study affirms that extraction using 1.3% citric acid pretreatment and the water bath method can produce chicken skin gelatin with good physicochemical characteristics. The implications of this study indicate the potential of broiler chicken skin as an alternative halal gelatin source that can be developed to support the value-added utilization of poultry waste.